PEMBERIAN INFUSED WATER ROSELLA (Hibiscus Sabdariffa L.) TERHADAP STABILISASI HEMODINAMIK (MEAN ARTERIAL PRESSURE AND PULSE PRESSURE) PADA PENDERITA HIPERTENSI A LITERATURE RIVIEW - Hariyono Hariyono (STIKES Insan Cendekia Medika Jombang, 2021)
Introduction: hypertension was a blood vessel disease and was the most common in the community. The administration of rosella (Hibiscus sabdariffa l. ) was used as a new way to reduce the risk of heart and blood vessel disease including hypertension, to stabilize mean arterial pressure and pulse pressure in hypertensive patients after infused rosella water and hibiscus sabdariffa l which was linked to the literature empirical published in the last five years. Researched methods: design: a literature review. Data sources from comprehensive electronic searched searches conducted on google scholar (2015-2020), PubMed (2015-2020), complementary index (2015-2020), oaister (2015-2020), articles used in this review were published in Bahasa English and Indonesian. Results: researched in the searched for 10 journals, found that consumption of roselle could reduce systolic blood pressure by an average of 5. 5% while diastolic blood pressure was 4. 0%. So that changes in mean arterial pressure and pulse pressure were more stable after consuming hibiscus sabdariffa l. Conclusion: Previous studies had shown that there was an effect of infused water rosella (Hibiscus sabdariffa l. ) on stabilization of mean arterial pressure and pulse pressure in hypertensive patients.